TINGKAT KEPUASAN WISATAWAN TERHADAP KUALITAS PELAYANAN SHUTTLE BUS KOMOTRA BALI DI CENTRAL PARK KUTA - Suardana, I Wayan; Suwena, I Ketut; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2013)
This research discus tourists satisfaction hwo using service of Shuttle Bus Komotra Bali. Shuttle Bus Komotra Bali is one of transportation located at Kuta area. This study aims to determine tourist satisfaction knowing what factors are important and need to be maintained to achieve the satisfaction of tourist. The data collection method in this study conducted by observation, interviews, and questioner. Types of data used is the qualitative quantitative data, whereas the data source is primary and secondary data. Technique of determining the sample using the quota sampling. Data analysis techniques using performance-level analysis and interests (Importance-Performance Analysis). From the results of research, it can be concluded that in general, tourists feel dissatisfactory with the performance or quality of services provided by the Shuttle Bus Komotra Bali with an average compliance rate of 72,22 percent of the respondents. The indicators are considered important and should be maintained to to increase satisfaction performance among other Transportation’s condition (2), ready to help with good of quality service and hospitality (5), trust to drivers (10). Based on the results of discussion, recommended to the Shuttle Bus Komotra Bali to maintain and even improve the performance or quality of service to the factor considered important bay tourist, so as to provide optimum satisfaction to the tourist, which in turn can be used as advantages by Shuttle Bus Komotra Bali compete with another transfrtation.
Keywords: Analysis, Quality and Tourist Satisfaction